Development of chemiluminescence method based on serum type I collagen hydroxyl terminal peptide β special sequence (β-CTX). (1st October 2021) - Huo, Zhen; Liu, Xueke; Wu, Yongfeng; Liang, Yong; Xu, Ruyue; Ma, Yongfang; Song, Li; Shen, Jing; Tang, Xiaolong
Abstract: The objective of this work is to develop and verify the analytical performance of a chemiluminescence immunoassay for the specific sequence β-carboxy-terminal cross-linking telopeptide of type I collagen (β-CTX) in human serum. Two specific monoclonal antibodies (mAb-8A03 and mAb-3D12) with high affinity for β-CTX were selected, and, under optimized conditions, a chemiluminescence immunoassay method (CLIA) for β-CTX was established. The CLIA of β-CTX detected β-CTX in a wide range of 2.0–6000 ng/L. The recovery rate in serum is 95–105%, the specificity is high, and the cross-reaction rate with common easily interfering substances is low (not more than 0.01%). The CLIA correlates well with Roche electrochemiluminescence immunoassay (ECLIA), with a correlation coefficient of 0.9551, which fully meets the requirements of clinical analysis. The developed β-CTX CLIA kit has high sensitivity and good stability. It has the same performance as the commercial Roche ECLIA kit and can be applied clinically.